Event-triggered robust control for networked control systems with actuator failures and time-varying transmission delays. Issue 2 (8th June 2015) - Pan, Peng; Jiang, Shun; Pan, Feng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is with robust control problem for event-triggered networked control systems (NCSs) with actuator failures and time-varying transmission delays. Design/methodology/approach – A random sequence is introduced to describe the actuator faults, and a novel event-triggering communication scheme is adopted in the sensor-to-controller channel. By taking the event-triggered mechanism and network transmission delay into consideration, a delay system model is constructed. Findings – Based on Lyapunov stability theory and free weighting matrix method, the feasibility criteria for co-designing both the controller gain and the trigger parameters are derived. Finally, a simulation example is exploited to demonstrate the effectiveness of the proposed linear matrix inequalities (LMIs) approach. Originality/value – The introduced approach is interesting for NCSs with actuator failures and time-varying transmission delays.